2023
DOI: 10.1177/09564624231152781
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to uptake of PrEP across the continuum among transgender women: A global scoping review

Abstract: Background Although preexposure prophylaxis (PrEP) has demonstrated high efficacy for HIV prevention, rates of PrEP uptake remain low among the transgender population, especially in transgender women (TGW). We conducted this scoping review to assess and characterize barriers to PrEP use along the PrEP care continuum among TGW. Methods We conducted this scoping review by searching studies in Embase, PubMed, Scopus, and Web of Science. Eligibility criteria included: reporting a PrEP related quantitative result a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…In this sample, these interactions took the form of exerted violence, low access to material resources [e.g., income, employment, and education], and discriminatory experiences when accessing healthcare. The context of sex work seems to be the intersection where all these negative forces combine and the effects are dual and paradoxical: on one hand, the perception of high risk of HIV acquisition seems to favour PrEP uptake, but on the other hand, the negative experiences are detrimental for PrEP access, adherence, and persistence [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this sample, these interactions took the form of exerted violence, low access to material resources [e.g., income, employment, and education], and discriminatory experiences when accessing healthcare. The context of sex work seems to be the intersection where all these negative forces combine and the effects are dual and paradoxical: on one hand, the perception of high risk of HIV acquisition seems to favour PrEP uptake, but on the other hand, the negative experiences are detrimental for PrEP access, adherence, and persistence [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Negative interactions with health services and their providers were also common narratives from the participants, which are comparable with other contexts, and would likely discourage PrEP uptake and adherence [ 21 ]. The experiences reported by TGW in our study prompt us to infer that sexual health education that is inclusive of gender diversity is lacking for Colombian healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, prior research with trans participants across other fields of research may inform this work. Recent quantitative studies have found that anti‐trans stigma, the dearth of trans‐inclusive sexual health programmes and medical mistreatment pose significant barriers to PrEP‐related care [2, 10, 15, 20–24]. Qualitative studies have aligned with these findings and further described how structural factors such as anti‐trans discrimination and disenfranchisement (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In light of these recommendations, tailored implementation strategies to achieve equitable PrEP delivery for trans populations are needed [3,13]. Regrettably, implementation studies rarely enrol trans participants in numbers sufficient to yield reliable estimates-transfeminine participants are often subsumed into study cohorts comprised predominantly of cisgender sexual minority men, while transmasculine and nonbinary individuals are rarely enrolled at all [13][14][15][16][17][18] Limited inclusion of trans participants in implementation research will hinder efforts to develop strategies that are salient and relevant to trans individuals who might otherwise benefit from PrEP due to their current sexual practices or personalized HIV prevention needs and preferences [3,13,15,19]. However, prior research with trans participants across other fields of research may inform this work.…”
Section: Introductionmentioning
confidence: 99%